Intra-patient comparison of parietal pleural biopsies by rigid forceps, flexible forceps and cryoprobe obtained during medical thoracoscopy: a prospective series of 80 cases with pleural effusion. Issue 1 (December 2016) - Wurps, H.; Schönfeld, N.; Bauer, T.; Bock, M.; Duve, C.; Sauer, R.; Mairinger, T.; Griff, S.
Abstract Background There is only few data available on the use of cryotechnique during medical thoracoscopy. Methods Medical thoracoscopy was performed in consecutive patients with pleural effusion. Prospectively, biopsies were taken by rigid forceps, flexible forceps and cryoprobe. Specimen size, depth and diagnostic yield were compared. Results 80 Patients were included. 408 biopsies were taken (205 rigid biopsies, 104 flexible biopsies, 99 cryobiopsies). Mean surface area of rigid biopsies was 22.6 ± 20.4 mm2 (flexible biopsies: 7.1 ± 9.3 mm2, cryobiopsies: 14.4 ± 12.8 mm2 ). Rigid biopsies were significantly larger than cryobiopsies (p  < 0.001) and flexible biopsies (p  < 0.001), crybiopsies were significantly larger than flexible biopsies (p  < 0.01). A deep biopsy containing fatty tissue was harvested in 63 % of rigid biopsies (cryobiopsy: 49.5 % flexible biopsy: 39.5 %). In 79/80 cases (98.7 % 95 % CI cannot be calculated) a diagnosis was obtained by rigid biopsy (cryobiopsy: 73/80 cases (91.3 % 95 % CI 86.0 – 96.5 %), flexible biopsy: 74/80 cases (92.5 % 95 % CI 88.6 – 97.4 %)). Diagnostic yield achieved with cryobiopsies was inferior to the yield of rigid biopsies (Difference: 12.7 %), but non-inferior to flexible biopsies (Difference: 6.5 %). Conclusion Cryobiopsies in medical thoracoscopy are safe with high diagnostic yield, non-inferior to flexible biopsies with increased tissue quantity and quality. Cryotechnique can develop an important role in medical thoracoscopy in the near future when rigid thoracoscopy is not available.